New immune horizons in therapeutics and diagnostic approaches to Preeclampsia. (2nd January 2023) - Mukherjee, Indrani; Singh, Sunil; Karmakar, Abhibrato; Kashyap, Neha; Mridha, Asit Ranjan; Sharma, Jai Bhagwan; Luthra, Kalpana; Sharma, Radhey Shyam; Biswas, Subhrajit; Dhar, Ruby; Karmakar, Subhradip
Abstract: Hypertensive disorders of pregnancy (HDP) are one of the commonest maladies, affecting 5%–10% of pregnancies worldwide. The American College of Obstetricians and Gynecologists (ACOG) identifies four categories of HDP, namely gestational hypertension (GH), Preeclampsia (PE), chronic hypertension (CH), and CH with superimposed PE. PE is a multisystem, heterogeneous disorder that encompasses 2%–8% of all pregnancy‐related complications, contributing to about 9% to 26% of maternal deaths in low‐income countries and 16% in high‐income countries. These translate to 50 000 maternal deaths and over 500 000 fetal deaths worldwide, therefore demanding high priority in understanding clinical presentation, screening, diagnostic criteria, and effective management. PE is accompanied by uteroplacental insufficiency leading to vascular and metabolic changes, vasoconstriction, and end‐organ ischemia. PE is diagnosed after 20 weeks of pregnancy in women who were previously normotensive or hypertensive. Besides shallow trophoblast invasion and inadequate remodeling of uterine arteries, dysregulation of the nonimmune system has been the focal point in PE. This results from aberrant immune system activation and imbalanced differentiation of T cells. Further, a failure of tolerance toward the semi‐allogenic fetus results due to altered distribution of Tregs such as CD4+FoxP3+ or CD4+CD25+CD127(low) FoxP3+ cells, thereby creating a cytotoxic environment by suboptimal production of immunosuppressive cytokines like IL‐10, IL‐4, and IL‐13. Also, intracellular production of complement protein C5a may result in decreased FoxP3+ regulatory T cells. With immune system dysfunction as a major driver in PE pathogenesis, it is logical that therapeutic targeting of components of the immune system with pharmacologic agents like anti‐inflammatory and immune‐modulating molecules are either being used or under clinical trial. Cholesterol synthesis inhibitors like Pravastatin may improve placental perfusion in PE, while Eculizumab (monoclonal antibody inhibiting C5) and small molecular inhibitor of C5a, Zilucoplan are under investigation. Monoclonal antibody against IL‐17(Secukinumab) has been proposed to alter the Th imbalance in PE. Autologous Treg therapy and immune checkpoint inhibitors like anti‐CTLA‐4 are emerging as new candidates in immune horizons for PE management in the future.